Quorum‐sensing signaling by chironomid egg masses' microbiota, affects haemagglutinin/protease (HAP) production by Vibrio cholerae. Issue 7 (22nd October 2020) - Sela, Rotem; Hammer, Brian K.; Halpern, Malka
Abstract: Vibrio cholerae, the causative agent of cholera, is commonly isolated, along with other bacterial species, from chironomid insects ( Diptera: Chironomidae ). Nevertheless, its prevalence in the chironomid egg masses' microbiota is less than 0.5%. V. cholerae secretes haemagglutinin/protease (HAP) that degrades the gelatinous matrix of chironomid egg masses and prevents hatching. Quorum sensing (QS) activates HAP production in response to accumulation of bacterial autoinducers (AIs). Our aim was to define the impact of chironomid microbiota on HAP production by V. cholerae . To study QS signaling, we used V. cholerae bioluminescence reporter strains (QS‐proficient O1 El‐Tor wild‐type and QS‐deficient mutants) and different bacterial species that we isolated from chironomid egg masses. These egg mass isolates, as well as a synthetic AI‐2, caused an enhancement in lux expression by a V. cholerae QS‐deficient mutant. The addition of the egg mass bacterial isolate supernatant to the QS‐deficient mutant also enhanced HAP production and egg mass degradation activities. Moreover, the V. cholerae wild‐type strain was able to proliferate using egg masses as their sole carbon source, while the QS‐deficient was not. The results demonstrate that members of the chironomid bacterial consortium produce external chemical cues that, like AI‐2, induce expression of the hapA gene in V. cholerae . Understanding the interactions between V. cholerae and the insects' microbiota may help uncover the interactions between this pathogen and the human gut microbiota. Abstract : see also the Perspective by Jonathan D. Oliver and Nicholas M. Fountain‐Jones.